The Catholic Student Movement in Bahía Blanca and Its National and Transnational Links (1968-1975) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
This article proposes to identify the specialized Catholic Action movements meant for student youth that developed in Bahía Blanca between 1968 and 1975 as part of the International Movement of Catholic Students (IMCS)- International Young Catholic Students (IYCS). To do so, this article reconstructs the relationships between the groups in Bahía Blanca with similar experiences pertinent to the same movement at both national and international levels, identifying its convergences and divergences in the crossroads between Liberation Catholicism and politics. As such, reflecting on the following questions: In what way did these lay movements articulate social networks in Argentina and Latin America? What type of interaction linked these actors? Which ideas, values, practices and common repertoires of social action constructed those links? On the basis of the foregoing, what particularities characterized the groups of catholic students in Bahía Blanca?
Keywords: Liberation Catholicism; Politics; International Catholic Student Movement; BahÃa Blanca